2014
DOI: 10.1002/ps.3755
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate‐resistant and glyphosate‐susceptible Palmer amaranth (Amaranthus palmeri S. Wats.): hyperspectral reflectance properties of plants and potential for classification

Abstract: GR and GS Palmer amaranth plants have unique hyperspectral reflectance properties, and there are four distinct regions of the spectrum that can separate the GR from GS plants. These results demonstrate that hyperspectral imaging has potential application to distinguish GR from GS Palmer amaranth plants (without a glyphosate treatment), with future implications for glyphosate resistance management. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…15,22 Among different biotypes of the same weed species, however, varying levels of enzymes [for instance, overproduction of the 5-enolpyruvylshikimate-3-phosphate (EPSP) synthase enzyme endowing resistance to glyphosate in glyphosate-resistant kochia and Palmer amaranth 20,23 ] produced by individuals (glyphosate-resistant versus susceptible biotype) can produce spectra that can be discriminated from one another.…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…15,22 Among different biotypes of the same weed species, however, varying levels of enzymes [for instance, overproduction of the 5-enolpyruvylshikimate-3-phosphate (EPSP) synthase enzyme endowing resistance to glyphosate in glyphosate-resistant kochia and Palmer amaranth 20,23 ] produced by individuals (glyphosate-resistant versus susceptible biotype) can produce spectra that can be discriminated from one another.…”
Section: Image Processingmentioning
confidence: 99%
“…biotypes can be distinguished using differences in reflectance across the near UV, visible, and near IR spectrum in laboratory conditions. 15 Further work using hyperspectral reflectance profiles has been done to predict the herbicide resistance of Palmer amaranth biotypes, 16 differentiate between glyphosate-susceptible and glyphosate-resistant Italian ryegrass, 17 and to detect the injury on crops as a result of dicamba and glyphosate. 18 Weeds also have been distinguished from crops using shape rather than spectral data, 19 but in our application there are no systematic shape differences between herbicide-resistant and herbicide-susceptible kochia plants.…”
Section: Introductionmentioning
confidence: 99%
“…could be differentiated from GS Palmer amaranth using hyperspectral technology. In a series of experiments with three different populations (two grown in a greenhouse, and one in the field), it was consistently demonstrated that GS and GR Palmer amaranth could be differentiated better than 94% of the time without the use of a glyphosate application [5].…”
Section: Introductionmentioning
confidence: 94%
“…Diminishing results are caused when there are not enough training samples to estimate joint probability distributions in high dimensional feature spaces [10]. In our previous research for differentiating GR and GS Palmer amaranth, the forward selection algorithm was conducted for spectral band selection [9]. The band selection process began with an empty set of selected bands.…”
Section: Band Selectionmentioning
confidence: 99%
“…In order to develop a rapid, non-destructive method for differentiating GR and GS weeds, Reddy et al [9] conducted a pilot study to differentiate GR Palmer amaranth (Amaranthus palmeri S. Wats.)…”
mentioning
confidence: 99%